2019
DOI: 10.1159/000495022
|View full text |Cite
|
Sign up to set email alerts
|

Differential Molecular Modeling Predictions of Mid and Conventional Dialysate Flows

Abstract: Background: High dialysate flow rates (QD) of 500–800 mL/min are used to maximize urea removal during conventional hemodialysis. There are few data describing hemodialysis with use of mid-rate QD (300 mL/min). Methods: We constructed uremic solute (urea, beta2-microglobulin and phosphate) kinetic models at varying volumes of distribution and blood flow rates to predict solute clearances at QD of 300 and 500 mL/min. Results: Across a range of volumes of distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Several studies revealed that dialysate flow higher than 500 ml/min was unhelpful for increasing the dialysis efficacy or infusion volume, with consequently important implications both from the ecological and economic points of view. [47][48][49] The CONVINCE study has recently started, enrolling 1800 patients in multiple European countries, with the main objective to compare standard high-flux HD and HDF, delivered in high volume (post-dilution >23 L/4 h session), in terms of morbidity, mortality, and Health-related Quality of Life. 50 This large, international, multicenter, randomized controlled trial, over a 3-year follow-up period, should finally deliver the undisputable answer about the superiority between the different dialytic techniques.…”
Section: Hemodiafiltration (Hdf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies revealed that dialysate flow higher than 500 ml/min was unhelpful for increasing the dialysis efficacy or infusion volume, with consequently important implications both from the ecological and economic points of view. [47][48][49] The CONVINCE study has recently started, enrolling 1800 patients in multiple European countries, with the main objective to compare standard high-flux HD and HDF, delivered in high volume (post-dilution >23 L/4 h session), in terms of morbidity, mortality, and Health-related Quality of Life. 50 This large, international, multicenter, randomized controlled trial, over a 3-year follow-up period, should finally deliver the undisputable answer about the superiority between the different dialytic techniques.…”
Section: Hemodiafiltration (Hdf)mentioning
confidence: 99%
“…Moreover, in post‐dilution HDF, the only recommendation concerning the dialysate, or dialysis fluid, refers to its purity. Several studies revealed that dialysate flow higher than 500 ml/min was unhelpful for increasing the dialysis efficacy or infusion volume, with consequently important implications both from the ecological and economic points of view 47‐49 …”
Section: Dialysis Techniquesmentioning
confidence: 99%
“…The maximum Qd accommodated by Tablo is 300 mL/min. A recent kinetic modeling analysis of the effect of decreasing Qd from 500 to 300 mL/min at Qb rates of 300–400 mL/min concluded that the resulting drop in equilibrated Kt/V urea would be relatively small at 0.12–0.22, a difference that could be nearly fully counteracted by using a dialyzer with a higher K O A (1480 versus 1170 mL/min) and extending treatment time by 15 min [ 30 ]. A recent in vivo study of six patients on maintenance dialysis sequentially treated with Tablo with a Qd of 300 mL/min and a conventional IHD machine (Gambro Phoenix) with Qd of 500 mL/min yielded clearance curves for urea, potassium, phosphate, and β 2 -microglobuin which were remarkably similar, with no statistically significant difference in the levels of any of the four solutes by the end of 4 h of treatment despite the differing Qd rates [ 27 ].…”
Section: Mini-reviewmentioning
confidence: 99%